Asymmetric synthesis of aryloxypropanolamines via OsO4-catalyzed asymmetric dihydroxylation - Sayyed, I. A.; Thakur, V. V.; Nikalje, M. D.; Dewkar, Gajanan; Kotkar, S. P.; Sudalai, A. (Tetrahedron, 2005)
A simple and effective procedure for the enantioselective synthesis of several beta-adrenergic blocking agents incorporating the first asymmetric synthesis of celiprolol, is described. The key steps are (i) sharpless asymmetric dihydroxylation of aryl allyl ethers to introduce chirality into the molecules and (ii) conversion of cyclic sulfates into the corresponding epoxides using a three-step procedure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: antihypertensive; asymmetric dihydroxylation; cyclic sulfates; epoxides

Titanium superoxide catalyzed selective oxidation of phenols to p-quinones with aq. H2O2 - Dewkar, Gajanan; Shaikh, T. M.; Pardhy, S.; Kulkarni, S. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
Titanium superoxide, a novel heterogeneous and readily accessible catalyst, is found to catalyze the selective oxidation of phenols to the corresponding 1,4-benzoquinones in preparative yields with aq. 30% H2O2 as oxidant under mild reaction conditions.

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide